Acute ACL reconstruction shows superior clinical results and can be performed safely without an increased risk of developing arthrofibrosis - von Essen, Christoffer (Knee Surg Sports Traumatol Arthrosc, 2019)
PURPOSE: To compare acute ACL reconstruction (ACLR) within 8 days of injury with delayed reconstruction after normalized range of motion (ROM), 6–10 weeks after injury. It was hypothesized that acute ACL reconstruction with modern techniques is safe and can be beneficial in terms of patient-reported outcomes and range of motion. METHODS: The effect of acute and delayed ACLR was randomized studied on 70 patients with high recreational activity level, Tegner level 6 or more, between 2006 and 2013. Patient-reported outcomes, objective IKDC, KOOS, and manual stability measurements were documented during the 24-month follow-up period. RESULTS: The acute ACLR group did not result in increased stiffness and showed superior outcome regarding strength and how the patient felt their knee functioning at 24 months. In addition, the acute group was not inferior to the delayed group in any assessment. Regarding patient-related outcomes in KOOS, both groups showed significant improvements in all subscales, but no difference was found between the groups. Functional return (FR) rate was almost double compared to the Swedish knee ligament register and treatment failure (TF) rate was reduced by half, no significant difference between the groups. No difference regarding cyclops removal, re-injury of ACL or meniscus was found between the two surgical timing groups. CONCLUSION: Acute ACLR within 8 days of injury does not appear to adversely affect ROM or result in increased stiffness in the knee joint and was not inferior to the delayed group in any assessment when compared to delayed surgery. LEVEL OF EVIDENCE: I.